Análise in vitro da infiltração bacteriana na interface de pilares protéticos e implantes com plataforma cone morse - Anjos, Carlos Magno dos (2009)
The existence of a microgap between the implant and the abutment allows the accumulation of a biofilm. The presence of bacteria in this region has been described as an etiologic factor for inflammatory processes, bringing as consequence tissue disorganization interfering in the long term peri-implant health. The objective of this study was to evaluate the existence of bacterial leakage between implants with Morse Taper platforms and abutments. The sample was divided in 3 groups with 10 specimens each: Neodent® implants with Neodent® abutments, Ankylos® implants with Ankylos® abutments and Ankylos® implants with Neodent® abutments. The inner part of the implants was inoculated with 0.1μl suspension of Escherichia coli. The abutments were screwed with the torque recommended by the manufacturers and the specimens were immersed in a broth culture MacConkey. The readings of the tubes containing the specimens after inoculation, which consisted of the presence or absence of turbidity due to bacterial growth were performed after 1, 2, 5, 7 and 14 days. Results demonstrated that none of the specimens presented turbidity of the culture medium, and the viability of the bacteria was confirmed through positive control test. It was concluded that the interfaces studied, pattern Cone Morse, prevented this strain of bacterial migration between the prosthesis and implants components.